Tuning magnetofluidic spreading in microchannels - Wang, Zhaomeng (2016)
Magnetofluidic spreading (MFS) is a phenomenon in which a uniform magnetic field is used to induce spreading of a ferrofluid core cladded by diamagnetic fluidic streams in a three-stream channel. Applications of MFS include micromixing, cell sorting and novel microfluidic lab-on-a-chip design. However, the relative importance of the parameters which govern MFS is still unclear, leading to non-optimal control of MFS. Hence, in this work, the effect of various key parameters on MFS was experimentally and numerically studied. Our multi-physics model, which combines magnetic and fluidic analysis, showed excellent agreement between theory and experiment. It was found that spreading was mainly due to cross-sectional convection induced by magnetic forces, and can be enhanced by tuning various parameters. Smaller flow rate ratio, higher magnetic field, higher core stream or lower cladding stream dynamic viscosity, and larger magnetic particle size can increase MFS. These results can be used to tune magnetofluidic spreading in microchannels.